Trigeminal neuralgia causes neurodegeneration in rats associated with upregulation of the CD95/CD95L pathway. (March 2020) - Wang, Lu; Long, Menghong; Wang, Maohua; Peng, Shuangchun; Chen, Guangxiang; Zhou, Jun; Ou, Cehua
Objectives: To explore the effects of trigeminal neuralgia on neurodegeneration in rats and the underlining mechanism. Methods: Sixty adult male Sprague Dawley rats were divided randomly into Chronic Constriction Injury of the Rat's Infraorbital Nerve (ION-CCI) group and sham group ( n = 30). Right suborbital nerve was ligated in ION-CCI group to establish a trigeminal neuralgia model. In sham group, suborbital nerve was exposed without ligation. Pain thresholds were measured before surgery and 1, 7, 15, and 30 days after surgery ( n = 10). Morris water maze tests ( n = 10) were conducted at 1, 15, and 30 days after surgery to evaluate the changes in learning and memory ability of rats. At 5, 19, and 34 days after surgery, serum S100β protein concentration and hippocampal Aβ1-42 protein expression were detected by enzyme-linked immunosorbent assay; total tau protein expression was detected by Western blotting; changes of neurons in hippocampus were observed by Nissl staining; and the expression of ser404 p-tau, cluster of differentiation (CD)95, CD95L, and cleaved caspase-3 proteins was detected by immunofluorescence and Western blotting. Results: Hyperalgesia occurred in ION-CCI group, and mechanical pain threshold decreased significantly ( P < 0.05). On the 15th and 30th days after surgery, ION-CCI group showed lower learning and memory ability than sham group ( P < 0.05). Serum S100β protein concentration, hippocampal A β1-42, and ser404 p-tau protein expression increased in the ION-CCI group 19 and 34 days after surgery ( P < 0.05), hippocampal CD95 expression increased in the ION-CCI group after surgery ( P < 0.05), hippocampal CD95L expression increased at 19 and 34 days after surgery ( P < 0.05), and cleaved caspase-3 expression increased at 5 and 19 days after surgery ( P < 0.05). Nissl bodies in ION-CCI group decreased significantly at 15 days after surgery. The expression of cleaved caspase-3 protein in ION-CCI group was positively correlated with the expression of CD95 and CD95L ( P < 0.05). Conclusions: Trigeminal neuralgia may lead to neuronal inflammation and neuronal apoptosis associated with upregulation of CD95/CD95L expression, thus causing neurodegeneration.